Effectiveness of Problem-Based Learning Assisted by Cleo Card to Improve Motivation and Learning Outcomes on the Periodic System of Elements Material - Ashfa, Ellisa Auliya; Priatmoko, Sigit; Sumarni, Woro; Haryani, Sri (Chemistry in Education, 2025)
Students still experience difficulties in understanding the concept of the periodic system of elements (PSE), as reflected in their low learning outcomes. One of the key factors influencing learning outcomes is learning motivation. Therefore, appropriate learning models and media are needed to improve both aspects. This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model assisted by Cleo Card in enhancing students' learning motivation and learning outcomes, as well as to analyze the relationship between motivation and learning outcomes on PSE material. The research employed a quasi-experimental design with a non-equivalent pretest-posttest control group design. The results showed that the application of the PBL model assisted by Cleo Card significantly improved students' learning motivation (%N-gain 64.14%, moderately effective) and learning outcomes (%N-gain 68.84%, moderately effective) compared to the control class. Mastery of motivation and learning outcomes in the experimental class reached 100% and 97.22%, respectively, while the control class only reached 47.22% and 8.33%. The t-test confirmed a significant effect of the PBL model with Cleo Card on both motivation and learning outcomes (p < 0.05). Furthermore, a strong and significant relationship was found between learning motivation and learning outcomes, with a correlation coefficient of 1.00 and a significance value of 0.297.